Use of probiotics in the production of pink shrimp postlarvae - Silva, Emanuell Felipe Beserra da; Fróes, Charles Nunes; Souza, Diego Moreira de; Soares, Roberta; Peixoto, Silvio; Wasielesky, Wilson; Ballester, Eduardo Luis Cupertino (Pesquisa Agropecuaria Brasileira, 2012)
<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The objective of this work was to evaluate the use of probiotics in the production of postlarvae of pink shrimp (<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPS-ItalicMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Farfantepenaeus brasiliensis<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">). A completely randomized experimental design was used, with two treatments – use of probiotics (<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPS-ItalicMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Bacillus <span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">spp.), and a control using antibiotic (erythromycin) –, and four replicates. Postlarvae in the PL<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 6pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">1 <span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">stage were stocked in each experimental unit (3.0 L) and cultured until stage PL<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 6pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">10<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">. Water quality variables and the development of the bacteria of the genus <span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPS-ItalicMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Vibrio<span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">, in the culture water, were monitored throughout the experiment. At the end of the experimental period, postlarvae were evaluated qualitatively and for survival, weight, and length. Regarding water quality variables, only nitrite was significantly higher in the antibiotic treatment. For the variables weight and length, there were no significant differences between treatments. No significant differences between treatments were observed in postlarvae quality and in the concentration of <span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPS-ItalicMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Vibrio <span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">spp. in the water. The use of antibiotics may be replaced by probiotics during production of <span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPS-ItalicMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">F. brasiliensis <span lang="EN-US" style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">postlarvae.